Comparison of the Effectiveness of Narrative Therapy and Structural Couple Therapy on Marital Burnout and Negative Emotions in Couples with a Physically Disabled Spouse in Ahvaz - Fathalipouri, Razie; Alavi, Seyedeh Zahra; Shahbazi, Masoud (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The objective of this study was to compare the effectiveness of narrative therapy and structural couple therapy in reducing marital burnout and negative emotional experiences among couples with a physically disabled spouse.Methods and Materials: This quasi-experimental study employed a pretest–posttest control group design with a two-month follow-up period. The statistical population included all couples with a physically disabled spouse who were registered at the Welfare Organization of Ahvaz in 2025. Using purposive–voluntary sampling, 30 eligible couples were selected and randomly assigned to two experimental groups (narrative therapy and structural couple therapy) and one control group, each consisting of 10 couples. Both interventions were delivered in eight weekly 90-minute sessions, while the control group received no intervention. Data were collected using the Marital Burnout Questionnaire and the Emotional Expressiveness Questionnaire (negative emotions subscale). Statistical analysis was conducted using repeated measures analysis of variance and Bonferroni post-hoc tests with SPSS version 22.Findings: Inferential analysis revealed significant main effects of time and group as well as significant time-by-group interactions for both marital burnout and negative emotions (p < 0.001). Bonferroni post-hoc comparisons indicated that both experimental groups showed significant reductions from pretest to posttest and from pretest to follow-up (p < 0.001), whereas the control group demonstrated no significant changes. No significant differences were found between the narrative therapy and structural couple therapy groups at posttest or follow-up, indicating comparable effectiveness of both interventions.Conclusion: Both narrative therapy and structural couple therapy were highly effective in reducing marital burnout and negative emotional experiences among couples with a physically disabled spouse, and these therapeutic gains were maintained over time.